Evaluasi terhadap Waktu Tunggu dan Jarak Berjalan Penumpang pada Perpindahan Moda di Stasiun Lempuyangan Yogyakarta - Yuwono Wiarco; Siti Malkhamah (Forum Teknik, 2005)
Lempuyangan Railway  Station is  located  in  Jogjakarta.  To  get  to  or  to  leave  the  station passengers  using  the  railway  services  take  other modes, such  as becak,  buses, taxis, and motorcycles (ojek). The  process of  mode  changing  is  very  importanl.  To  do so,  passengers  have to  walk  to  the  next  mode  stop  and  sometimes they  have to  wait for the  vehicle  arrival.  Research was undertaken  to investigate  the  performance  of  the  mode  changing  process,  in terms  of waiting  time and walking  distance,  based  on  site measurement  and  on what passengers perceived,  to  model the  relationship  between  the  performance  expected  and what  perceived  by the  passengers,  and to  evaluate  the  performance  using  standards set  by Directorate General of Land  Transport.  It  was found that  based  on both direct measurement  and  passengers perception,  the  performance  of  the changing  process  was  good.  There was a very good relationship between  what expected  and  what  perceived  by passengers.  The  waiting  time  and walking  distance  met  the  standards  required.Kata  kunci:  perpindahan  moda,  waktu  tunggu,  jarak  berjalan  kaki.